The Role of Accountant Professional Commitment in the Relationship of Cloud Computing Services to the Performance of Startup Companies in Indonesia - Ratih Kusumastuti; Derist Touriano; Dedy Setiawan; Wirmie Eka Putra; Lismawati; Dri Asmawanti (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to examine the effect of cloud computing services on the performance of startup companies in Indonesia, as well as to identify the mediating role of professional accountants' commitment in enhancing the effectiveness of digital technology adoption. The background of the study indicates that the rapid growth of startups, including those achieving unicorn status, is driven by digital transformation and the implementation of cloud computing, which increases operational flexibility, cost efficiency, and strategic innovation (Adjei et al., 2021; Elmorshidy, 2019; Khayer et al., 2020). On the other hand, the role of professional accountants is critical in managing risks and ensuring the integrity of financial management; thus, their commitment mediates the relationship between cloud computing adoption and startup performance (Kusumastuti et al., 2016; Mangiuc, 2017; Vasileiou & Kerr, 2021). Primary data were collected through an online survey using purposive sampling among professional accountants in the startup sector in Indonesia. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of IBM SPSS and WarpPLS version 7.0. The results reveal that cloud computing services have a significant positive effect on startup performance, and this effect is further enhanced when supported by a high level of professional accountants' commitment. These findings confirm that the synergy between technological capabilities and competent human resources is key to digital transformation and to enhancing the competitive advantage of companies in the era of globalization. The implications of this study underscore the need for investment in digital infrastructure and the improvement of human resource competence, particularly among professional accountants, to support innovative strategies and operational efficiency in startup environments. This research contributes both empirically and conceptually to the literature on digitalization and corporate performance.